VCE legal case studies - Lapsanas, Kathy (Oxford University Press, 1994)
Designed for VCE Legal Studies Units 3 and 4, this text focuses on the extent to which legal and non-legal dispute resolutions achieve just outcomes. Discusses aspects of the Australian legal system such as law making, areas of change and reform, and the relationship of law to society. Includes review questions and an index. The authors are experienced teachers